1979
DOI: 10.1113/jphysiol.1979.sp013010
|View full text |Cite
|
Sign up to set email alerts
|

Isopotentiality and an optical determination of series resistance in Limulus ventral photoreceptors.

Abstract: 3. From these measurements, as well as from calculations for a model spherical cell, we conclude that membrane potential can be controlled to within 2 mV using our micropipette 'point clamp' methods, for all but the brightest stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Fernandez & Nickel (1976) made an estimate based on both methods in crayfish and Muri, Coles & Baumann (1976) (Fioravanti & Fuortes, 1972). Because of this striking contrast, and because of the scatter of our results (particularly the ratio of C measured in the dark and in the light) it was desirable that the conclusion should be confirmed by other methods: this has been done by Brown et al (1979) Spread of excitation from a photoisomerized rhodopsin molecule It has been shown that in the photoreceptor of the leech the light-induced increase in membrane conductance occurs on, or close to, the microvilli (Fioravanti & Fuortes, 1972). In squid and honey bee drone, experiments with localized illumination have shown that the light-induced increase in membrane conductance is confined to regions of the cell not more than 10-20 ,um from the site of light absorption and that there are no marked variations in light sensitivity along the length of the rhabdome (Hagins, Zonana & Adams, 1965;Carreras, 1978).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Fernandez & Nickel (1976) made an estimate based on both methods in crayfish and Muri, Coles & Baumann (1976) (Fioravanti & Fuortes, 1972). Because of this striking contrast, and because of the scatter of our results (particularly the ratio of C measured in the dark and in the light) it was desirable that the conclusion should be confirmed by other methods: this has been done by Brown et al (1979) Spread of excitation from a photoisomerized rhodopsin molecule It has been shown that in the photoreceptor of the leech the light-induced increase in membrane conductance occurs on, or close to, the microvilli (Fioravanti & Fuortes, 1972). In squid and honey bee drone, experiments with localized illumination have shown that the light-induced increase in membrane conductance is confined to regions of the cell not more than 10-20 ,um from the site of light absorption and that there are no marked variations in light sensitivity along the length of the rhabdome (Hagins, Zonana & Adams, 1965;Carreras, 1978).…”
Section: Discussionmentioning
confidence: 96%
“…The present work addresses the question of how this saturation occurs. METHODS Photoreceptor cells of the superfused ventral rudimentary eye of Limulu8 polyphemu8 were impaled with two micro-electrodes much as described by Millecchia & Mauro (1969b) (see also Brown et al 1979). The superfusate was an artificial sea water of composition: NaCl, 423 mM; KCl, 10 mM; MgCl2, 22 mM; MgSO4, 26 mM; CaC12, 10 mm; Tris Cl buffer, 10 mM; pH 7-8.…”
mentioning
confidence: 99%
“…1 W cm-2 corresponded to approximately 2 x 1010 photons 8-1 absorbed by the cell. Micropipettes filled with 2 M-KCI were used to record membrane voltage and to pass voltage-clamp current as described previously (Millecchia & Mauro, 1969a,b;Brown, Harary & 382 CALCIUM AND PHOTORECEPTOR EXCITATION Waggoner, 1979). Ionophoretic injections were made into a voltage-clamped cell from a third intracellular micropipette.…”
Section: Electrophysiologymentioning
confidence: 99%
“…The factor by which the peak of the receptor potential initially increased was in the range 12-9. Some cells were impaled by two or three micropipettes and the sensitivity (defined as the peak light-induced current per unit irradiance) was measured by a voltage clamp (Brown et al 1979 (Millecchia & Mauro, 1969a). Therefore we do not ascribe all the increased responsiveness to an artifact of impalement.…”
Section: Cells Bathed In Egta-aswmentioning
confidence: 99%
“…It is now possible to optically measure changes in the membrane potential (for reviews see COHEN and SALZBERG,1978;WAGGONER,1979).Merocyaninerhodanine dyes have been used as rapid molecular probes to monitor action potentials in various nervous systems (WOOLUM andSTRUMWASSER,1978 COHEN et al,1978;GRINVALD et al,1981;Ross and REICHARDT,1979;BROWN et al, 1979).In addition,the merocyanine-rhodanine dyes were also applied to contractile tissues. BAYLOR and CHANDLER(1978)and NAKAJIMA and GILAI(1980) measured optical action potential in frog skeletal muscle stained with a merocyaninerhodanine dye(Dye XVII),and spontaneous action potentials were monitored in early embryonic chick hearts in normal solution FuJII et al, 1980FuJII et al, ,1981a.…”
mentioning
confidence: 99%